Stereotyping and generalizing and its impact on Polish-Jewish relations. About „Our Class” by Tadeusz Słobodzianek and „Jew” by Artur Pałyga - Prędka, Katarzyna (Free your mind: Reflections on language, literature and culture, 2022)
The article describes the most common examples of stereotypes and genealisations about Jews which appeared throughout Polish history. The author focuses on two modern dramas – “Our Class” by Tadeusz Słobodzianek and “Jew” by Artur Pałyga. Both of the stories show how much stereotyping affected negatively Polish-Jewish relations.